(untitled) (Research, Society and Development, 2020)
To report the experience about the formation process of founding students of the Academic League of Urgency and Emergency. This is an account of the experience of students in the nursing course. The educational activities of the Academic League of Urgency and Emergency of a Public University of the State of Minas Gerais, were conducted by fifteen students and three teachers and took place between the months of October to December 2019. The theoretical and practical contents were conducted by teachers and health professionals with expertise in the subject. The active and interactive pedagogy used in the events favored the formation of critical and socially responsible students to clinical situations that involve the population. The University’s Academic Urgency and Emergency League was founded through a meeting held with five undergraduate nursing students, who shared a common ideal: studying and researching urgency and emergency. The initiative to create the Academic League provided a training of qualified professionals to directly meet the demands of society.